Experimental and Simplified Predictive Determination of Extinction Coefficients of Ceramic Open‐Cell Foams Used for Metal Melt Filtration. Issue 2 (17th September 2021) - Heisig, Lisa-Marie; Markuske, Katrin; Werzner, Eric; Wulf, Rhena; Fieback, Tobias M.
Abstract : A main application area of ceramic open‐cell foams is the foundry, where the porous media are used for conditioning and filtration of the melt flow. As characterization of heat transfer in such high‐temperature applications requires consideration of thermal radiation, knowledge of the radiative properties of the foams is essential. Instead of elaborative measurements or simulations, empirical correlations often serve as a simple and fast method to predict extinction coefficients. However, significant differences up to 100 m −1 occur between calculated values of various models presented in the literature. Herein, it is aimed to characterize the radiation behavior of different ceramic foams experimentally and identify reliable, simple yet accurate methods for the prediction of extinction coefficients of these materials by comparison with experimental results. The influences of pore density (10 and 20 pores per inch [ppi]) and filter material (Al2 O3, ZrO2, SiC, Al2 O3 −C) on the transmittance, reflectance, and extinction coefficients are investigated by spectroscopic measurements. Two models from the literature are determined, which are well suited to predict extinction coefficients with an average deviation of less than 20%. Furthermore, accurate estimation with an average deviation of 12% can be also achieved using a projection method based on computed tomography scans of the foams. Abstract : Thermal radiation behavior and extinction coefficients of different ceramic open‐cell foams used for metal melt filtration are investigated by spectroscopic measurements. As an alternative to the experiments, selected models from the literature or a projection method based on computed tomography scans of the foam can be applied for a simple and fast prediction of extinction coefficients with acceptable accuracy.